Bismuth-Immobilized Optical Fiber-Based SPR Nanosensor for Detection of Zinc Nitrate Contamination in Aquaculture Industry - Yesudasu Vasimalla; Nasih Hma Salah; Baljinder Kaur; Hogr M. Rasul; Chella Santhosh; Ramachandran Balaji; S.R. Srither; Santosh Kumar (IEEE Open Journal of Nanotechnology)
Zinc nitrate, a toxic substance usually found in industrial waste and agricultural residues, poses a serious threat to the aquaculture industry due to the poor water quality and harmful aquatic life. Effective monitoring of zinc nitrate contamination is essential to protect aquatic ecosystems and also ensures the safety of aquaculture products. This study presents a bismuth-immobilized optical fiber-based surface plasmon resonance (SPR) biosensor for the rapid detection of zinc nitrate contamination. The sensor design incorporates a ZBLAN core, NaF cladding, silver (Ag) as a plasmonic metal, and bismuth (Bi) to enhance detection sensitivity. In our work, we compared the sensor performance of the proposed bismuth-immobilized SPR biosensor with the conventional Ag-based sensor design. The performance of the proposed Ag-Bi sensor model is compared with the conventional Ag-based sensor. To improve the sensitivity and FOM, Ag layer thickness is varied between 50 and 80 nm with respect to the zinc nitrate concentrations of 0%, 1%, and 5%. Using the angular interrogation method, the resonance wavelength shifts are correlated to changes in refractive index (RI). The Bi-immobilized Ag layer achieved a maximum sensitivity of 5680 nm/RIU at 5% zinc nitrate concentration and an FOM of 95.2381 RIU−1 at 1%. While conventional Ag-based sensors attained a maximum sensitivity of 5240 nm/RIU and an FOM of 90.345 RIU−1 at 80 nm Ag thickness. The above results demonstrate that the Ag-Bi layer SPR biosensor is highly suitable for simultaneously detecting zinc nitrate and other heavy metal contaminants in water, providing a cost-effective solution for heavy metal contamination detection in aquatic industry.